Mining-induced displacement and resettlement policies and local people's livelihoods in Ghana. Issue 6 (18th August 2021) - Oware Twerefoo, Portia
ABSTRACT: The mining industry is often associated with decisions that have huge social significance. Using the example of the AGL mining company and the Damang community in Ghana, this study sought to assess the extent of adherence to government policies as well as the implications of resettlement on the livelihood dynamics of the affected communities. The paper argues that the existing policies create a new type of poverty by widening the poverty gap. Furthermore, the actual practice adopted for the computation and payment of both land and cash compensation clearly seems to be in violation of the principle of fair compensation.